SKRINING FITOKIMIA DAN UJI POTENSI ANTIKANKER EKSTRAK METANOL KULIT BATANG (Rhizophora mucronata (Lamk.)) MENGGUNAKAN METODE BSLT (Brine Shrimp Lethality Test) - Asniyah, Asniyah; Mahmiah, Mahmiah; Sudjarwo, Giftania Wardani (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2023)
Cancer is one of the leading causes of death in the world. The main therapies for cancer include surgery, chemotherapy, radiotherapy. However, the use of chemotherapy drugs can cause side effects such as hair loss, bone marrow suppression, drug resistance. Based on these side effects, this study conducted research on natural ingredients as an alternative to cancer treatment. Rhizophora mucronata can be used as an anticancer, where people in coastal areas or around mangrove forests use mangroves as medicinal plants, and are believed to have minimal side effects so that they can be developed as traditional medicines. In this study, analysis of phytochemical screening and anticancer potential tests of methanol extract of Rhizophora mucronata stem bark was carried out from Pamurbaya, Surabaya, East Java. In this study, the BSLT (Brine Shrimp Lethality Test) method was used to test the anticancer potential with the LC50 (Letal Concentration) value as a parameter. The results of phytochemical screening of the methanol extract of Rhizophora mucronata stem bark contain tannins, saponins, alkaloids, steroids, flavonoids, anthraquinones and polyphenols and have anticancer potential with an LC50 value of 120.8656 ppm which falls into the toxic category.